Structured assessments on the desire for activities – ‘Why wish for what I can’t do?’ - M. Granbom (Scandinavian Journal of Occupational Therapy)
Introduction Homecare services are limited, and there is likely a gap between the everyday activities homecare users want to do and the activities they perform or receive help with. Structured assessment on the desire for engaging in activities may be useful to identify unmet occupational needs.Aim To reflect on the experiences of using the Occupational Gaps Questionnaire (OGQ) to investigate how homecare users express the desire to do everyday activities they know they cannot perform without help, and to deepen the understanding of how the desire of doing may be restricted beyond limitations in language and cognition.Method OGQ interviews were conducted with 11 older adults who received daily homecare. The interviews were analysed thematically.Result/discussion The homecare users reported few occupational gaps. Activities that were previously part of their occupational repertoire and considered to be meaningful were no longer desired. The desire to engage in activities appears to be influenced by functional decline and the structural limitations of homecare. Structured assessments might not capture the full picture of what a person desires to do, however may spark valuable conversations. For person-centered eldercare, professionals must acknowledge how functional decline and structural limitations influence what older adults desire to do.